Does Traditional Islamic Malay Literature Contain Shi‘itic Elements? ‘Ali and Fātimah in Malay Hikayat Literature - Edwin Wieringa (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1996)
Many experts of classical Malay literature argues that Persian influence is known very well to the traditional Malay literature. This is evident from a number of Malay literary texts are very popular, such as Saga Bakhtiar, Hikayat Amir Hamzah, Hikayat Muhammad Hanafiyah and The Book of the Thousand Known issues is a kind of adaptation or translation even langsungdari Persian texts. Key issue of this paper is wanted to be appointed; whether there is influence in the Persian classical Malay literature was once an indication of the influence of Shiite against Sunni Islam which evolved from the beginning of the archipelago?DOI: 10.15408/sdi.v3i4.795